Antibiotic treatment failure in four common infections in UK primary care 1991-2012: longitudinal analysis. - Currie, C; Berni, E; Jenkins-Jones, S; Poole, C; Ouwens, M; Driessen, S; de Voogd, H; Butler, C; Morgan, C (BMJ Publishing Group, 2014)
OBJECTIVE: To characterise failure of antibiotic treatment in primary care in the United Kingdom in four common infection classes from 1991 to 2012. DESIGN: Longitudinal analysis of failure rates for first line antibiotic monotherapies associated with diagnoses for upper and lower respiratory tract infections, skin and soft tissue infections, and acute otitis media. SETTING: Routine primary care data from the UK Clinical Practice Research Datalink (CPRD). MAIN OUTCOME MEASURES: Adjusted rates of treatment failure defined by standardised criteria and indexed to year 1 (1991=100). RESULTS: From 58 million antibiotic prescriptions in CPRD, we analysed 10,967,607 monotherapy episodes for the four indications: 4,236,574 (38.6%) for upper respiratory tract infections; 3,148,947 (28.7%) for lower respiratory tract infections; 2,568,230 (23.4%) for skin and soft tissue infections; and 1,013,856 (9.2%) for acute otitis media. In 1991, the overall failure rate was 13.9% (12.0% for upper respiratory tract infections; 16.9% for lower respiratory tract infections; 12.8% for skin and soft tissue infections; and 13.9% for acute otitis media). By 2012, the overall failure rate was 15.4%, representing an increase of 12% compared with 1991 (adjusted value indexed to first year (1991) 112, 95% confidence interval 112 to 113). The highest rate was seen in lower respiratory tract infections (135, 134 to 136). While failure rates were below 20% for most commonly prescribed antibiotics (amoxicillin, phenoxymethylpenicillin (penicillin-V), and flucloxacillin), notable increases were seen for trimethoprim in the treatment of upper respiratory tract infections (from 29.2% in 1991-95 to 70.1% in 2008-12) and for ciprofloxacin (from 22.3% in 1991-95 to 30.8% in 2008-12) and cefalexin (from 22.0% in 1991-95 to 30.8% in 2008-12) in the treatment of lower respiratory tract infections. Failure rates for broad spectrum penicillins, macrolides, and flucloxacillin remained largely stable. CONCLUSIONS: From 1991 to 2012, more than one in 10 first line antibiotic monotherapies for the selected infections were associated with treatment failure. Overall failure rates increased by 12% over this period, with most of the increase occurring in more recent years, when antibiotic prescribing in primary care plateaued and then increased.